Oxygen isotope evolution of biogenic calcite and apatite during the Middle and Late Devonian - Joachimski, Michael; Geldern, Robert; Breisig, Stephan; Buggisch, Walter; Day, Jed; van Geldern, Robert (International Journal of Earth Sciences, 2004)
Oxygen isotope ratios of well-preserved brachiopod calcite and conodont apatite were used to reconstruct the palaeotemperature history of the Middle and Late Devonian. By assuming an oxygen isotopic composition of -1‰ V-SMOW for Devonian seawater, the oxygen isotope values of Eifelian and early Givetian brachiopods and conodonts give average palaeotemperatures ranging from 22 to 25 °C. Late Givetian and Frasnian palaeotemperatures calculated from δO values of conodont apatite are close to 25 °C in the early Frasnian and increase to 32 °C in the latest Frasnian and early Famennian. Oxygen isotope ratios of late Givetian and Frasnian brachiopods are significantly lower than equilibrium values calculated from conodont apatite δO values and give unrealistically warm temperatures ranging from 30 to 40 °C. Diagenetic recrystallization of shell calcite, different habitats of conodonts and brachiopods, as well as non-equilibrium fractionation processes during the precipitation of brachiopod calcite cannot explain the O depletion of brachiopod calcite. Moreover, the O depletion of brachiopod calcite with respect to equilibrium δO values calculated from conodont apatite is too large to be explained by a change in seawater pH that might have influenced the oxygen isotopic composition of brachiopod calcite. The realistic palaeotemperatures derived from δO may suggest that biogenic apatite records the oxygen isotopic composition and palaeotemperature of Palaeozoic oceans more faithfully than brachiopod calcite, and do not support the hypothesis that the O/O ratio of Devonian seawater was significantly different from that of the modern ocean. © Springer-Verlag 2004.
Keywords: Brachiopod calcite; Conodont apatite; Devonian; Oxygen isotopes; Palaeotemperature